The Development of the Urung Senembah Kingdom and Its Legacy in Patumbak, 1620-2023: Perkembangan Kerajaan Urung Senembah dan Peninggalannya Di Patumbak, 1620-2023 - Muhammad Akbar Maulana; Jufri Naldo (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research aims to study the history of the development of the Urung Senembah kingdom in Patumbak from 1620 to 2023, with a focus on the development of the kingdom, history and Islam. This research uses historical research methods in four steps: heuristics, criticism, interpretation, and historiography. Data was collected from relevant archives, books, articles and reports. This research focuses on the Urung Senembah kingdom, which was founded by the Barus family and had authority over the Deli and Serdang Sultanates. The territory of this kingdom stretches from the Seruai River to thelumai River. This research uses primary and secondary sources, including history books, government reports, and contemporary documents. This study aims to complete research on the Urung Senembah kingdom and its significance in the history of Patumbak.